Protective effect of famotidine, omeprazole, and melatonin against acetylsalicylic acid-induced gastric damage in rats - (:unkn) unknown (SPRINGER, 2001)
It has been reported that both omeprazole and famotidine have a protective effect against gastric mucosal damage induced by acetylsalicylic acid (ASA) and other nonsteroidal antiinflammatory drugs, Since active oxygen species and lipid peroxidation were reported to play a role in the pathogenesis induced by ASA, we aimed to study if omeprazole and famotidine have any antioxidant effect by comparing their protective effect with that of melatonin, an effective antioxidant and free radical scavenger. Mucosal damage was evaluated by macroscopic examination, histological analysis and by measurement of lipid peroxidation (LPO), glutathione (GSH), and myeloperoxidase (MPO) activity. Omeprazole (20 mu mol/kg per os), famotidine (3 mg/kg per os), and melatonin (10 mg/kg intraperitoneally) significantly prevented gastric ulcerogenesis induced by ASA (200 mg/kg per as) and decreased the ulcer index. Gastric LPO and MPO activity that were increased significantly by ASA were decreased after treatment with omeprazole, famotidine, and melatonin. ASA treatment decreased significantly the gastric GSH levels, and pretreatment with omeprazole, famotidine, or melatonin increased it significantly. Famotidine and omeprazole decreased the gastric acidity, which was increased by ASA, whereas melatonin had no effect on this parameter. These findings suggest that active oxygene species and LPO have an important role in the pathogenesis of gastric mucosal damage induced by ASA and that both famotidine and omeprazole may be protective against this damage, although they were not as efficient as melatonin as an antioxidant. On the other hand, the antisecretory effect of omeprazole and famotidine may also be contributing to their antiulcer effect.
Keywords: acetylsalicylic acid; gastric mucosal injury; omeprazole; famotidine; melatonin; glutathione; lipid peroxidation; LIPID-PEROXIDATION; MUCOSAL INJURY; FREE-RADICALS; ANTIOXIDANT PROPERTIES; ISCHEMIA-REPERFUSION; L-TRYPTOPHAN; ETHANOL; GLUTATHIONE; INDOMETHACIN; LESIONS